Concentrations dominated membrane permeability variation by fullerol nanoparticles on a single living HeLa cell. Issue 34 (15th August 2016) - Liu, Naiyun; Han, Mumei; Zhang, Yalin; Wu, Xiuqin; Liu, Juan; Li, Hao; Cao, Tiantian; Nan, Xueyan; Huang, Hui; Liu, Yang; Chen, Ning; Wang, Chunru; et al.
Abstract : The effects in HeLa cell membrane permeability caused by the fullerenols C60 (OH) n with different concentrations were studied by scanning electrochemical microscopy (SECM). Abstract : The effects in HeLa cell membrane permeability caused by the fullerenols C60 (OH) n with different concentrations were studied by scanning electrochemical microscopy (SECM). We demonstrate that C60 (OH) n has very low cytotoxicity, although it can still have strong effects on the cell membrane permeability. In the presence of 1 × 10 −3 mg mL −1 (1 ppm) C60 (OH) n, the cell membrane permeability increases by 26% after 76 min, which is reversible. When C60 (OH) n concentration is over 25 × 10 −3 mg mL −1 (25 ppm), the change in membrane permeability (increased 19%) is irreversible.